A Data Collection Framework for Care Coordination and Clinical Communications About Patients (CAPs). Issue 1 (June 2013) - Zachary, Wayne; Maulitz, Russell; Iverson, Elissa; Onyekwelu, Chioma; Risler, Zachary; Zenel, Lauren
Care coordination unfolds through communications about specific patients between clinicians in the context of a specific illness episode. This is a largely informal process that is also ephemeral, in that it leaves little or no permanent documentary record. Recent research has identified care coordination and communication about patients as a potential solution for improving care for chronic illnesses while reducing health care costs and increasing accountability, and as vehicle for reducing medical errors. However, relatively few empirical data exist on the communications about patients that comprise care coordination, possibly due to the methodological difficulty in gathering such data. A theory-based and empirically refined method for representing and collecting data on CAPs is presented.